Philadelphia chromosome-positive B-cell acute lymphoblastic leukemia with e13a3 fusion transcripts in a patient with pre-existing essential thrombocythemia: a case report and literature review - Wu, Ying; Cao, Dan (Frontiers in Oncology, 2025)
Essential thrombocythemia (ET), a BCR-ABL1-negative myeloproliferative neoplasm (MPN), is characterized by persistent thrombocytosis and excessive megakaryocytic proliferation in the bone marrow. During the course of the disease, 4% of patients progress to acute leukemia, the majority of which have acute myeloid leukemia (AML), and are confirmed to be transformed from ET. Transformation to acute lymphoblastic leukemia (ALL) is exceedingly rare, with limited evidence clarifying its clonal relationship to antecedent ET. We report a case of a 66-year-old man with a history of ET, lacking mutations in Janus kinase 2 (JAK2), Calreticulin (CALR), or myeloproliferative leukemia virus oncogene (MPL), who subsequently developed Philadelphia chromosome (Ph)-positive B-cell ALL (B-ALL), harboring a rare e13a3 fusion transcript. Following four cycles of induction therapy with olverembatinib, vincristine, and prednisone, the patient achieved complete hematologic and molecular remission. A chemotherapy-free consolidation therapy with olverembatinib and blinatumomab maintained sustained complete molecular remission at follow-up. To our knowledge, this represents the first case of Ph-positive B-ALL with e13a3 transcripts arising in a patient with preexisting ET, providing critical therapeutic insights for managing similar cases.